HIV risk-taking behaviours as consequences of HIV knowledge and perceived risk of HIV among university undergraduates (2010)
This study examined knowledge and perceived risk of HIV infection as factors likely to affect HIV risk-taking behaviours. Two hundred and sixty nine undergraduates of the University of Ibadan participated in this cross-sectional survey (154 male and 115 female). Data were collected using three structured and validated scales. Results indicated that HIV knowledge has a significant effect on HIV risk-taking behaviours. Perceived risk of HIV also has a significant effect on risk-taking behaviours. It was concluded that inadequate/inappropriate knowledge of HIV, increases HIV risk-taking behaviours. Attitudes that personal efforts do not affect health outcomes also increases HIV risk-taking behaviours. It is thus recommended that HIV awareness campaigns be intensified, while attitudinal change initiatives should be embarked upon to discourage HIV risk-taking behaviour.